Large-scale physical modelling of soil-filled masonry arch bridges. Issue 2 (8th February 2017) - Augusthus-Nelson, Levingshan; Swift, Gareth; Melbourne, Clive; Smith, Colin; Gilbert, Matthew
Abstract : The presence of soil backfill has been shown to have a significant influence on the load-carrying capacity of masonry arch bridges, with the soil fill providing a number of important functions, including inter alia, the distribution of surface loads and passive resistance to arch deformation during loading. Large-scale physical modelling allows high-quality data to be collected under controlled conditions, while enabling essential aspects of the interaction between the soil fill, the masonry arch and the abutments to be observed. This paper considers the design and construction of a unique test facility that allows large-scale soil-filled masonry arch structures to be studied under both quasi-static and cycling loading regimes. The key challenges that were needed to be overcome to develop this facility are presented and discussed.